2016
DOI: 10.1002/2016sw001375
|View full text |Cite
|
Sign up to set email alerts
|

On the origins and timescales of geoeffective IMF

Abstract: Southward interplanetary magnetic field (IMF) in the geocentric solar magnetospheric (GSM) reference frame is the key element that controls the level of space weather disturbance in Earth's magnetosphere, ionosphere, and thermosphere. We discuss the relation of this geoeffective IMF component to the IMF in the geocentric solar ecliptic (GSE) frame, and using the almost continuous interplanetary data for 1996–2015 (inclusive), we show that large geomagnetic storms are always associated with strong southward, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 129 publications
(191 reference statements)
1
93
0
Order By: Relevance
“…The probability of a change in B z polarity is also generally higher near perihelion than near aphelion. Lockwood et al [] (their Figure 14) show that in near‐Earth interplanetary space, the overall probability of a B z polarity change after 4 h is 0.83, which is lower than the average in all panels of Figure for such a lag. Hence, the difference between perihelion and aphelion found here is a trend that continues with increasing heliocentric distance to r = 1 AU.…”
Section: Resultsmentioning
confidence: 99%
“…The probability of a change in B z polarity is also generally higher near perihelion than near aphelion. Lockwood et al [] (their Figure 14) show that in near‐Earth interplanetary space, the overall probability of a B z polarity change after 4 h is 0.83, which is lower than the average in all panels of Figure for such a lag. Hence, the difference between perihelion and aphelion found here is a trend that continues with increasing heliocentric distance to r = 1 AU.…”
Section: Resultsmentioning
confidence: 99%
“…For B N , however, the RMSE for persistence is higher than climatology even at a lead time of two hours, demonstrating the short autocorrelation time in the B N time series and the inherent difficulty in B N prediction (e.g. Lockwood et al, 2016 and references therein).…”
Section: Performance Of the Deterministic Solar-wind Anen Over 1996 -mentioning
confidence: 96%
“…For space-weather forecasting purposes, the radial solar-wind flow speed [V R ] and the component of the HMF normal to the solar-rotation plane [B N ] are the critical parameters, as they are the primary contributors to the dawn-to-dusk electric field that controls reconnection with the magnetospheric field (Dungey, 1961). Owing to the inclination of the Earth's magnetosphere and orbital plane to the solar-rotation plane, the HMF component along the solar-rotation direction [B T ] also leads to a magnetic field anti-parallel to the nose of the magnetosphere, in a manner that varies systematically with both day of year and time of day (Lockwood et al, 2016). The solar-wind density [N P ] also affects the compression of the magnetosphere and hence the efficiency of the magnetic coupling between the heliospheric and magnetospheric magnetic fields.…”
Section: Producing An Ensemble Analogue (Anen) For the Solar Windmentioning
confidence: 99%
“…Lockwood et al . [] have recently shown that larger storms are caused by coronal mass ejections that generate more persistent southward interplanetary magnetic field. Further, multiple magnetic storms sometimes occur within several days, and the major driver of such multiple storms is also a series of coronal mass ejections [ Kataoka and Miyoshi , ].…”
Section: Introductionmentioning
confidence: 99%